PERANCANGAN SISTEM INFORMASI E-COMMERCE PENJUALAN PERABOT JATI JEPARA MENGGUNAKAN METODE CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA TOKO CV.CAHAYA FURNITURE DENGAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL - Jihan Anisa (LPPM Politeknik Jambi, 2023)
CV. Cahaya Furniture is a CV engaged in furniture crafts such as guest chairs, cupboards, dining tables, beds and others. CV. Cahaya Furniture finds it difficult to manage product data and transactions and ordering or purchasing goods. With e-commerce to promote various -various Jepara teak furniture at CV.Cahaya Furniture makes it easy for users by not meeting in person to make transactions but simply using a computer connected to the internet and also an ordering information system that can use the PHP programming language and MySQL database in making transactions and can make it easier for employees to check and preparing reports. The existence of a marketing strategy based on efforts to create relationships between the company and customers, better known as Customer Relation Management, is expected to be able to make customers loyal to the company so that the relationship that occurs is not only the relationship between the seller and the customer. sales and buyers, but more towards a partner relationship, and Customer Relationship Management can increase sales and competitiveness.